Ni–Co–O solid solution dispersed nanocrystalline Co3O4 as a highly active catalyst for low-temperature propane combustion. Issue 21 (5th September 2018) - Cai, Ting; Yuan, Jing; Zhang, Lin; Yang, Ling; Tong, Qin; Ge, Meiying; Xiao, Bei; Zhang, Xiaolan; Zhao, Kunfeng; He, Dannong
Abstract : Highly active nanocrystalline Co3 O4 dispersed on Ni–Co–O solid solution surface for propane combustion. Abstract : Co3 O4 and NiO have been widely studied as catalysts for catalytic combustion because of their high oxygen mobility, both theoretically and experimentally. Research into their combination to make highly dispersed nanocrystalline Co3 O4 is rare. Here we prepared a Ni–Co–O solid solution dispersed nanocrystalline Co3 O4 of NiO–Co(0.3) as a highly active and stable catalyst for propane combustion by a simple co-precipitation method. Superior to pure oxides, the specific rate (μmolC3 gcat −1 h −1 ) of NiO–Co(0.3) at 170 °C is 2.5 times as high as pure Co3 O4, whereas the pure NiO is inert at this temperature. The nanocrystalline Co3 O4 particles surrounded by active O species are the main active sites for NiO–Co(0.3) catalyst. The synergistic effects between the nanocrystalline Co3 O4 particles and Ni–Co–O solid solution with high oxygen mobility give the high propane combustion activity. Further research shows that the highly active performance relates directly to the surface Co content, Co 2+ species and active O species. Our findings offer insight into the preparation of highly active nanocrystalline Co3 O4 dispersed on transition oxides, which is different to that previously reported.